Sala de Aula - dos lugares fixos aos entrelugares fluidos - Maria Teresa Esteban (Universidade do Minho, 2006)
The classroom is marked by the difference, many times naturalized and devoidof its ambiguous content. Adiscursive plot is created which deviates the focusof exclusion of the different ones, kept out of school or cloistered in devaluedspaces in the school routine, to the exclusion of the different oneswho jointhe classroom with the democratization of school access. The transformationof the school discourse about the difference and the constant redefinition ofthe pedagogical devices tip off of the tension between homogeneity/heterogeneity which constitutes the classroom routine. The performance ofpedagogic dynamics linked to favorable school results of working classchildren demands dialogue, which demands the recognition of these childrenas practice, knowledge and sense producers; as subjects who also havepower in the shaping of educational relations, the learning/teaching processand the classroom dynamics